Genetic Recombination in Bacteriophage φX174 - Benbow, Robert M. (1974)
Genetic recombination in bacteriophage φX174 usually takes place early in the infection process and involves two parental replicative form (double-stranded) DNA molecules. The host recA protein is required; none of the nine known φX174 cistron products is essential. The products of a single recombination event are nonreciprocal and asymmetric. Typically, only one of the parental genotypes and one recombinant genotype are recovered from a single cell. An alternative, less efficient recombination mechanism which requires an active φX174 cistron A protein is observed in the absence of the host recA gene product.